Division shaped substrate integrated waveguide slot antenna for millimeter wireless/automotive radar applications. (October 2018) - Nanda Kumar, M.; Shanmuganantham, T.
Abstract: A dual-band Substrate Integrated Waveguide (SIW) based slot antenna is presented, it's excited by microstrip line and size is 4 × 9.034 × 0.381 mm 3 . The Computer Simulation Technology(CST) studio suite software is used to design and simulate the proposed design. The rogers substrate material is used in this design which is a dielectric constant of 2.2 and thicknesses used is 0.381 mm. The proper alignment of the division shaped slot will resonate the two frequencies those are 60 GHz, 79 GHz and also analyze the antenna parameters like voltage standing wave ratio (VSWR), reflection coefficient, radiation patterns, surface current, efficiencies and gain. The RLC equivalent circuit model is introduced to verify the proposed design reflection coefficient and VSWR. The matrix laboratory (MATLAB) software is used to analyze the equivalent model and validated the simulation results.